1992
DOI: 10.1209/0295-5075/17/3/011
|View full text |Cite
|
Sign up to set email alerts
|

Single-Electron Pump Based on Charging Effects

Abstract: We have designed and operated a device consisting of three nanoscale tunnel junctions biased below the Coulomb gap. Phase shifted r.f. voltages of frequency f applied to two gates “pump” one electron per cycle through the device. This is shown experimentally by plateaus in the current-voltage characteristic at I = ± ef, the sign of the current depending on the relative phase of the r.f. voltages and not on the sign of the bias voltage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
434
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 507 publications
(438 citation statements)
references
References 9 publications
4
434
0
Order By: Relevance
“…4). Several attempts to create a metrological current source that would comply with the demanding criteria of extreme accuracy, high yield and implementation with not too many control parameters have been reported [5][6][7][8][9][10][11] . Here, we propose and prove the unexpected concept of a hybrid normal-metalsuperconductor turnstile in the form of a one-island singleelectron transistor with one gate, which demonstrates robust current plateaux at multiple levels of e f at frequency f .…”
mentioning
confidence: 99%
“…4). Several attempts to create a metrological current source that would comply with the demanding criteria of extreme accuracy, high yield and implementation with not too many control parameters have been reported [5][6][7][8][9][10][11] . Here, we propose and prove the unexpected concept of a hybrid normal-metalsuperconductor turnstile in the form of a one-island singleelectron transistor with one gate, which demonstrates robust current plateaux at multiple levels of e f at frequency f .…”
mentioning
confidence: 99%
“…1-3 Several approaches to obtain such a quantized current pump have been tested. [4][5][6][7][8] However, obtaining both a high current value and a high accuracy has proven to be difficult. Recently, Blumenthal et al have demonstrated a new promising way to deliver high currents.…”
mentioning
confidence: 99%
“…If we choose the dc gate charges n g1 and n g2 far from the boundaries but within the (0,0) cell, then because of the large electrostatic energies we can assume that the system remains in the state |00 . Strictly speaking, this charge stability diagram [57] is only valid in the absence of Josephson coupling; however, it also remains valid for small Josephson coupling, except at the boundaries where the charge states become superposed. Since the pulse gate has equal coupling to each qubit, the application of a pulse shifts the state of the system on this diagram along the line tilted at 45 degrees (indicated by arrows in Fig.…”
Section: Coherent Dynamics Of Two Charge Qubitsmentioning
confidence: 99%